Paramedics providing end-of-life care: an online survey of practice and experiences - Natasha Campling; Joanne Turnbull; Alison Richardson; Sarah Voss; Jennifer Scott-Green; Shane Logan; Sue Latter (BMC Palliative Care)
Abstract Background Global demand for care during the last year of life (end-of-life) is rising and with shortfalls in community healthcare services, paramedics are increasingly called on to deliver this. Despite this growing demand on the paramedic workforce, little large-scale or detailed empirical research has evaluated current practice and paramedic experiences of attending this patient group. Therefore, as part of a wider study evaluating paramedic delivery of end-of-life care, a large-scale survey in England describing paramedics’ current practice and experiences providing end-of-life care was undertaken. Methods A cross-sectional online survey design. Quantitative data were analysed using descriptive statistics and qualitative free text responses using Framework Analysis. The survey link was distributed to registered paramedics employed by all 11 NHS Trusts employing paramedics in England, United Kingdom. Results Nine hundred and twenty responses were received. They reported shortfalls in availability of healthcare professionals for advice and/or referral. Respondents often, always or sometimes: lacked patient medical history (91%, 839), access to existing advance care planning documentation (98%, 900) and specific medicines needed (80%, 737); encountered conflicting views (89%, 819); and reported lack of pre-registration training (81%, 743) or continuing professional development (77%, 708) influenced their ability to meet patient needs. Conclusions This first national survey of paramedic practice and experiences in delivering end-of-life care provides new evidence and insight into the challenges faced by paramedics and the potential impact of these challenges on their perceived levels of competence and confidence. Respondents reported multiple challenges, which potentially impact their ability to provide good quality end-of-life care and increase the risk of hospital conveyance. Paramedic practice at end-of-life must be supported via improved access to: patient records; anticipatory medicines and authority to administer; 24/7 palliative care advice (for shared decision-making); and paramedic specific palliative and end-of-life care training and education (including via integrative ways of working between palliative care and ambulance services). Action is required to integrate paramedicine within the wider healthcare professional team, with robust education and training to support care delivery.